A Comparative Study of Different Amendments on Amelioration of Saline-Sodic Soils Irrigated with Water Having Different EC: SAR Ratios. Issue 22 (16th December 2017) - Murtaza, Ghulam; Murtaza, Behzad; Kahlon, Umad Zafar; Yaseen, Muhammad
ABSTRACT: Soil degradation affects soil properties such as structure, water retention, porosity, electrical conductivity (EC), sodium adsorption ratio (SAR), and soil flora and fauna. This study was conducted to evaluate the response of contrasting textured soils irrigated with water having different EC:SAR ratios along with amendments: gypsum (G), farm manure (FM), and mulch (M). Water of different qualities viz. EC 0.6 + SAR 6, EC 1.0 + SAR 12, EC 2.0 + SAR 18, and EC 4.0 + SAR 30 was used in different textured soils with G at 100% soil gypsum requirement, FM at 10 Mg ha −1, and M as wheat straw was added on surface soil at 10 Mg ha −1 . Results revealed that the applied amendments in soils significantly decreased pHs and electrical conductivity (ECe ) of saturated paste and SAR. Four pore volumes of applied water with leaching fraction 0.75, 0.77, and 0.78 removed salts 3008, 4965, and 5048 kg ha −1 in loamy sand, silty clay loam, and sandy clay loam soils, respectively. First four irrigations with LF of 0.82, 0.79, 0.75, and 0.71, removed 5682, 5000, 3967, and 2941 kg ha −1 salts, respectively. The decreasing order for salt removal with amendments was FM > G > M > C with LF = 0.85, 0.84, 0.71, and 0.68, respectively. This study highlights a potential role of soil textures to initiate any mega program for reclamation of saline-sodic soils in the perspective of national development strategies.